Clinical Characterization of Epilepsy of Unknown Cause in Cats. (16th November 2013) - Wahle, A.M.; Brühschwein, A.; Matiasek, K.; Putschbach, K.; Wagner, E.; Mueller, R.S.; Fischer, A.
<x xml:space="preserve">Abstract</x> Background The diagnosis of feline epilepsy of unknown cause (EUC) requires a thorough diagnostic evaluation, otherwise the prevalence of EUC could be overestimated. Hypothesis Feline EUC is a clinically defined disease entity, which differs from feline hippocampal necrosis by the absence of magnetic resonance imaging (MRI) signal alteration of the hippocampus. The objectives of this study were (1) to evaluate the prevalence of EUC in a hospital population of cats by applying well‐defined inclusion criteria, and (2) to describe the clinical course of EUC. Animals Eighty‐one cats with recurrent seizures. Methods Retrospective study—medical records were reviewed for cats presented for evaluation of recurrent seizures (2005–2010). Inclusion criteria were a defined diagnosis based on laboratory data, and either MRI or histopathology. Final outcome was confirmed by telephone interview with the owner. Magnetic resonance images were reviewed to evaluate hippocampal morphology and signal alterations. Results Epilepsy of unknown cause was diagnosed in 22% of cats with epilepsy. Physical, neurologic, and laboratory examinations, and either 1.5 T MRI and cerebrospinal fluid analysis or postmortem examination failed to identify an underlying cause. Cats with EUC had a higher survival rate (P < .05) and seizure remission occurred frequently (44.4%). Conclusion and Clinical Importance A detailed clinical evaluation and diagnostic imaging with MRI is recommended in any cat with recurrent seizures. The prognosis of cats with normal MRI findings and a clinical diagnosis of EUC are good. Standardized imaging guidelines should be established to assess the hippocampus in cats.